Utilization of Magnesium for the Treatment of Chronic Pain - Urits, Ivan (Anesth Pain Med, 2021)
CONTEXT: The International Association for the Study of Pain (IASP) defines chronic pain as pain that persists or recurs for longer than 3 months. Chronic pain has a significant global disease burden with profound effects on health, quality of life, and socioeconomic costs. EVIDENCE ACQUISITION: Narrative review. RESULTS: There are several treatment options, including pharmacological therapy, physical rehabilitation, psychological therapies, and surgical interventions, for chronic pain management. Magnesium has been FDA-approved for several indications including hypomagnesemia, arrhythmia, prevention of seizures in eclampsia/preeclampsia, and constipation. Magnesium has been used for numerous off-label uses, notably for acute and chronic pain management. The mechanism of magnesium in pain management is primarily through its action as a voltage-gated antagonist of NMDA receptors, which are involved in pain transduction. CONCLUSIONS: This narrative review will focus on the current evidence and data surrounding the utilization of magnesium as a treatment option for chronic pain.